Science Across the Abyss: Knitting Bridges with Butterflies - Bacquet Perez, Caroline Nicole; Batres, Jorge (Organisms. Journal of Biological Sciences, 2024)
Science is built on the pursuit of answers to fundamental questions and the constant expansion of our understanding of the world around us. However, this effort has not been without challenges and inequalities. This article critically examines the issue of diversity in science and the notable disparities that persist in global scientific knowledge. Throughout history, the contributions of scientists from diverse regions and cultures have been pivotal to scientific advancement. Nevertheless, significant gaps in terms of access, funding, and recognition in the global scientific community still endure. We use the concept of the "abyss," as a metaphor for the disparities in scientific practices across diverse regions of the world within the context of globalization. We seek to shed light on how the abyss influences the very essence of scientific inquiry, ranging from disparities in access to knowledge to the limitations imposed by technology and resources. This article addresses how socioeconomic, gender, and geographical disparities impact who has the opportunity to engage in and lead scientific research. The decolonization of science and the incorporation of indigenous and local perspectives in research are highlighted as crucial ways to address these disparities. Additionally, the concept of participative science is explored as an inclusive approach that allows diverse communities to take part in scientific research. Ultimately, this exploration of diversity in science and disparities in scientific knowledge seeks to inspire deeper reflection on how we can work together to ensure that science becomes a truly global and representative endeavor, enriched by a multitude of perspectives and the collaboration of people from all corners of the world.